Enhanced selectivity of carbonaceous products from electrochemical reduction of CO2 in aqueous media. (March 2019) - Xiang, Hang; Rasul, Shahid; Scott, Keith; Portoles, Jose; Cumpson, Peter; Yu, Eileen H.
Graphical abstract: Highlights: Gas diffusion electrodes enhanced the selectivity of carbonaceous products. High hydroxide concentrations led to faster kinetics and lower activation energy. High alkalinity stabilized oxygen surface group for oxide derived Cu catalysts. C2 Faradic Efficiency of 40%, maximum current density of −234 mA cm −2 achieved. Abstract: This study highlights the importance of CO2 supply method and impact of electrolyte alkalinity in aqueous electrochemical CO2 reduction using Cux O catalyst. Two different CO2 supply methods using a two-chamber (2C) cell with CO2 purging into catholyte and a CO2 gas diffusion electrode (GDE) cell were compared. Faradaic efficiency (FE) of carbonaceous products in GDE cell was more than 3-folds higher than the 2C cell due to improved CO2 mass transfer. From the investigation of alkaline catholyte in GDE cell, the higher catholyte alkalinity led to higher current density and higher FE of carbonaceous products with a better selectivity of C2 (ethanol and ethylene). The reason lies in the OH groups around catalyst surface which improve the reaction kinetics and moreover stabilize the catalyst surface oxygen during the reduction process. With the potential of −1.17 V (RHE) in 2.0 M KOH, C2 FE of 40% and current density of −234 mA cm −2 were achieved. The production rate of ethylene and ethanol was respectively 0.105 mg min −1 and 0.035 mg min −1 on 2 cm 2 electrode with CO2 flow rate 15 ml min −1, which are promising for further development and scale-up.